Books and Monographs Received (Review of Economic Studies, 1940)
Journal Article Books and Monographs Received Get access The Review of Economic Studies, Volume 8, Issue 1, October 1940, Page 66, https://doi.org/10.2307/restud/8.1.66 Published: 01 October 1940